Preparation and immune in chickens of pulsatile delivery system for inactivated Newcastle disease vaccine - Jun Li (Asian Pacific Journal of Tropical Medicine, 2018)
Due to the weak immunogenicity, traditional inactivated vaccines need to use adjuvants and multiple doses to generate effective immune protection. Therefore, in theory and practice, it is valuable to develop a vaccine delivery system with an adjuvant effect, which can be carried out in a single dose. In view of this, inactivated Newcastle disease virus (NDV)-loaded poly (lactic-co-glycolic acid) (PLGA) microspheres with different release characteristics were prepared. Two release peaks of four groups of microspheres were observed during in vitro release test. The first release peak came out on the first day. The second release peak of A microspheres appeared at the 7th week. The second release peak of B microspheres appeared at the 5th week. The second release peaks of C and D microspheres all appeared at the 11th week. The release of C microspheres contrast to D microspheres was more smooth at release peak, so A, B, C microspheres were selected to construct the pulsatile system. Thus inactivated Newcastle disease(ND) vaccine pulsatile release systems using an appropriate combination of vaccine microspheres with a suitable release characteristics was constituted . Then their immune effects on chickens were evaluated. Chickens without maternal antibodies against NDV were grouped randomly and then immunized with NDV-PLGA microsphere vaccine and inactivated ND vaccine respectively. The results show that inactivated NDV-PLGA microsphere vaccine had the effect of pulsatile release in chickens and were able to maintain high and constant antibody level. And the pulsatile release system composed of mixed microspheres had the best immune effect. This study demonstrated that inactivated NDV-PLGA microsphere pulsatile release system with reasonable release interval could realize effective immune protection in a long time by a single injection. This was the first ever report on PLGA microspheres-based pulsatile release system for inactivated NDV vaccine.